Using EPR to follow reversible dihydrogen addition to paramagnetic clusters of high hydride count: [Rh(6)(PCy(3))(6)H(12)](+) and [Rh(6)(PCy(3))(6)H(14)](+). - Hiney, R; Chaplin, AB; Harmer, J; Green, J; Weller, A (2010)
A combined structural/EPR/computational chemistry investigation is reported on the two paramagnetic hydrido-cluster salts [Rh(6)(PCy(3))(6)H(12)][BAr(F)(4)] and [Rh(6)(PCy(3))(6)H(14)][BAr(F)(4)], the latter being formed by reversible addition of H(2) to the former, [BAr(F)(4)](-) = [B{C(6)H(3)(CF(3))(2)}(4)](-). The solid-state structure of [Rh(6)(PCy(3))(6)H(14)][BAr(F)(4)] shows an expanded cluster core compared to previously reported [Rh(6)(PCy(3))(6)H(12)][BAr(F)(4)] indicative of the addition of hydrogen to the cluster surface. This expansion correlates well with the calculated (PH(3) replaces PCy(3)) structures. EPR measurements on [Rh(6)(PCy(3))(6)H(12)][BAr(F)(4)] indicate two isomers at low temperature, which are tentatively assigned as diastereomers that result from locked phosphine rotation and bridging hydride/semi bridging hydride tautomerism. The EPR signal disappears above 60 K which is suggested to occur due to fast Raman-type relaxation-a phenomenon consistent with the calculated small SOMO/SOMO - 1 and SOMO/LUMO gaps. For [Rh(6)(PCy(3))(6)H(14)][BAr(F)(4)] EPR measurements indicate two isomers, the proportion of which change with temperature and deuteration-one axial isomer and one rhombic isomer. DFT calculations on a number of plausible isomers give EPR parameters which fit the experimentally determined rhombic isomer to one in which there is an interstitial hydride in the cluster and thirteen hydride ligands on the surface, while the axial isomer has two dihydrogen-like ligands on the cluster surface. That these isomers lie close in energy comes from both the EPR measurements (as measured from equilibrium constants over a variable temperature range) and DFT calculations. Deuteration of the hydrides should favour the isomer with the lowest zero-point energy and this is the case, with the axial isomer (two D(2) ligands on the surface) being favoured over the rhombic.